Agreement and predictive power of six fall risk assessment methods in community-dwelling older adults. (March 2020) - Menezes, Michele; de Mello Meziat-Filho, Ney Armando; Araújo, Camila Santos; Lemos, Thiago; Ferreira, Arthur Sá
Highlights: Personalized detection of risk of falling varies among assessment methods. Assessment methods moderately agree to identify who is at high risk of falling. Questionnaires outperform posturography to detect the risk of falling in older adults. Abstract: A large number of fall risk assessment methods are available with a variety of performances for screening the risk of falling in older adults, but their agreement for assessing the risk of falling remains unknown. This observational prospective cohort study describes the agreement and predictive power of methods to classify the risk of falling in older adults using prospective data and published cut-off values. Fifty-two participants aged 74 years (interquartile range 69–80) were assessed using the Berg Balance Scale, polypharmacy, Falls Risk Assessment Score, Fall Risk Assessment Tool, Fall Efficiency Scale, and Posturography. Nine participants (17 %) reported at least one fall after six months. Cochran's test showed different proportions of participants classified as at high risk of falling among all methods ( Q = 69.560, p < 0.001). A slightly better-then-chance agreement was estimated between all FRA methods (Light's κ = 0.074, 95%CI [0.021; 0.142]). We found both global and pairwise agreement levels that question the agreement among fall risk assessment methods for screening community-dwelling older adults.